Polymer Nanocomposites: Fabrication of Graphene Nanoplatelet/Epoxy Nanocomposites for Lightweight and High‐Strength Structural Applications (Part. Part. Syst. Charact. 6/2018). (22nd June 2018) - Kim, Joonhui; Cha, Jaemin; Jun, Gwang Hoon; Yoo, Sung Chan; Ryu, Seongwoo; Hong, Soon Hyung
Abstract : An ultra‐light and high‐strength Graphene nanoplatelets (F‐GNPs)/epoxy nanocomposite was achieved using a strategy of non‐covalent functionalization by melamine as represented in the image. In article1700412, Joonhui Kim and co‐workers demonstrate the incorporation of melamine drives exceptionally enhanced mechanical properties of the nanocomposite via homogeneous dispersion and enhanced interfacial cohesion between GNP flakes and epoxy matrix.